Sistem E-Payroll pada Karyawan Yayasan Pendidikan Islam An-Nadwah Menggunakan Algoritma Advanced Encryption Standard (AES) Berbasis Web - Linda Fitriyani; Dwipa Handayani; Tyastuti Sri Lestari; Agus Hidayat (Journal of Students‘ Research in Computer Science, 2025)
The rapid development of information technology encourages educational institutions to improve efficiency and security in administrative management, including payroll systems. This research aims to design a web-based E-Payroll system implemented at the Islamic Education Foundation An-Nadwah by applying the Advanced Encryption Standard (AES) algorithm to ensure the confidentiality of employee salary data. The system was developed using the Rapid Application Development (RAD) method to enable fast and user-responsive development. The implementation results show that the system can effectively encrypt and decrypt salary data, as well as provide real-time and secure payroll reports. System testing using the blackbox method demonstrates that all system functionalities work as expected. This system is expected to enhance efficiency, accuracy, and security in the payroll process within the foundation.